COMPARACIÓN DE UNA PRUEBA DE ELISA ESTÁNDAR Y ELISA DE RANGO EXTENDIDO PARA LA ENFERMEDAD INFECCIOSA DE LA BURSA EN AVES - Salas M., Magali (2002)
A total of 180 paired serum samples from 3 breeder groups (broiler’s grandparents and parents), and layers) were used to detect antibodies against the Infectious Bursal Disease virus through the ELISA test. Animals were tested at three ages (1-3 days, 16, and 27 weeks of age). Two commercial kits were tested: the standard ELISA (ELISA-IBD) and the new named Extended Range ELISA (ELISA-XR). The latter detected higher titres of antibodies than the ELISA-IBD. Broiler’s parents had the higher levels of antibodies indicating better immune response than the other two groups. The titre distribution had a more uniform distribution using the ELISA-IBD rather that the ELISA-XR; however all titres were above the minimum accepted ranges when the ELISA-XR was used (p<0.05). The results indicated that the new ELISA-XR was more efficient in detecting antibodies against the Infectious Bursal Disease virus.